Lifetimes of Arabidopsis cryptochrome signaling states in vivo. (15th March 2013) - Herbel, Vera; Orth, Christian; Wenzel, Ringo; Ahmad, Margaret; Bittl, Robert; Batschauer, Alfred
Summary One crucial component in light signaling is the quantity of photoreceptor present in the active signaling state. The lifetime of the signaling state of a photoreceptor is limited because of thermal or otherwise back reversion of the chromophore to the ground state, and/or degradation of the photoreceptor in the light‐activated state. It was previously shown that the lit state of plant cryptochromes contains flavin‐neutral semiquinone, and that the half‐lives of the lit state were in the range of 3–4 min in vitro. However, it was unknown how long‐lived the signaling states of plant cryptochromes are in situ. Based on the loss of degradation of cry2 after prolonged dark incubation and loss of reversibility of photoactivated cry1 by a pulse of green light, we estimate the in vivo half‐lives of the signaling states of cry1 and cry2 to be in the range of 5 and 16 min, respectively. Based on electron paramagnetic resonance measurements, the lifetime of the Arabidopsis cry1 lit state in insect cells was found to be 6 min, and thus very similar to the lifetime of the signaling state in planta. Thus, the signaling state lifetimes of plant cryptochromes are not, or are only moderately, stabilized in planta.